Barriers to implement the industrialised building system in Malaysia / Muhammad Hanif Hashim - Hashim, Muhammad Hanif (Faculty of Architecture, Planning and Surveying, 2015)
Industrialised building system (IBS) is not new to the construction industry. IBS is a construction method where all or part of the building components of the structure such as column, beam, slab is fabricated or precast in the factory or on site and assembled on site. IBS was introduced in Malaysia since 1964. The usage of IBS in the construction was encouraged by CIDB for the advantages of IBS such as less construction time, saving in labours, less wet job on site better quality control and etc. In our country this system is not widely used due the barriers of implementation such as lack of knowledge in IBS system and so on. This study is focused on precast concrete structure only. It is also to know issues and challenges implementation on precast building and to identify the disadvantages IBS system therefore an understanding about barrier implement IBS system, issues and challenges and lastly disadvantages will be discussed in this report. Questionnaires survey was conducted in order to achieve the objectives. The respondents consisted of contractors, architects, and local authority .At the end of the study, based on the knowledge from literature review, questionnaire and observation some recommendation about IBS system practice might improves in the future.